Electronic skin as wireless human-machine interfaces for robotic VR - Liu, Yiming; Yiu, Chunki; Song, Zhen; Huang, Ya; Yao, Kuanming; Wong, Tszhung; Zhou, Jingkun; Zhao, Ling; Huang, Xingcan; Nejad, Sina Khazaee; Wu, Mengge; Li, Dengfeng; et al. (Science advances, 2022)
The closed-loop HMI system could compliantly interface with human body for teleoperating various robotics with haptic feedback. The coronavirus pandemic has highlighted the importance of developing intelligent robotics to prevent infectious disease spread. Human-machine interfaces (HMIs) give a chance of interactions between users and robotics, which play a significant role in teleoperating robotics. Conventional HMIs are based on bulky, rigid, and expensive machines, which mainly focus on robots/machines control, but lack of adequate feedbacks to users, which limit their applications in conducting complicated tasks. Therefore, developing closed-loop HMIs with both accurate sensing and feedback functions is extremely important. Here, we present a closed-loop HMI system based on skin-integrated electronics, whose electronics compliantly interface with the whole body for wireless motion capturing and haptic feedback via Bluetooth, Wireless Fidelity (Wi-Fi), and Internet. The integration of visual and haptic VR via skin-integrated electronics together into a closed-loop HMI for robotic VR demonstrates great potentials in noncontact collection of bio samples, nursing infectious disease patients and many others.